Sistem Koperasi Simpan Pinjam Dan Pembiayaan Syariah BMT AT-TAQWA Berbasis Web - Asep Yudistira Saputra; Safitri Ristanti; Sultan Rafly Sya’Ban; Thoyyibah T. (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Cooperatives have existed since 1905 and their purpose is to provide a means of maintaining economic stability. However, in reality, cooperatives have not been the people's first choice. Because of these problems, researchers are interested in further examining the role of the Sharia Savings and Loans Cooperative (KSPPS) in strengthening the community's economy. The purpose of this study was to determine the role of (KSPPS) in strengthening the community's economy and the driving and inhibiting factors of KSPPS BMT Attaqwa in improving people's welfare. This research is a field research with qualitative descriptive. In collecting data, the authors used the interview method as a guide for BMT AT-TAQWA staff while documentation was carried out through notes or information obtained from BMT At-Ataqwa such as: History, organizational structure and financial description of BMT AT-TAQWA. The result of this study is the role (KSPPS) in accordance with sharia principles. With the role of BMT AT-TAQWA towards its members, namely providing business capital, meeting the consumption needs of members, providing Qord loan funds and social funds, strengthening the economy with savings programs. The driving factors and inhibiting factors of KSSP BMT, the driving factors for the welfare of its members use internal factors, namely; Employee Rules and BMT At-Ataqwa and external factors, namely: demographic factors are influenced by education, age of maturity and gender. geographic factor; country, city, town, region. The factors that impede the improvement of members' welfare are: The inability of BMT AT-TAQWA staff to market their products which many people still don't know about BMT.